ANTI-CORRUPTION AUDIT OF COMPANIES AND FORESIGHT ANALYSIS IN TERMS OF THE STATE'S EUROPEAN INTEGRATION ECONOMIC POLICY - Анастасія Майстренко; Каріна Назарова; Тетяна Копотієнко; Роман Овчарик; Вікторія Міняйло; Наталія Шалімова (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article examines the current problems of spreading corruption in Ukraine. It has been established that corruption is a negative socio-economic phenomenon that restrains the state's economic development, reduces trust in the authorities and complicates the fight against Russia's military aggression. The coming years will be indicative for Ukraine's international partners in the context of assessing the effectiveness of national anti-corruption policy, and the degree of implementation of planned anti-corruption reforms, which will indicate the level of integration of European values into society and Ukraine's readiness to become a full member of the EU. The perception of the main corruption problems by the public and business was analyzed, and it was established that the general attitude of Ukraine towards corruption is shifting towards intolerance of this negative phenomenon. Based on the analysis of the dynamics of detected financial violations by the State Audit Service of Ukraine in the region for 2019-2023, the TOP-3 conditional regions that are prone to violations, including corruption, have been determined. A trend analysis of the volume of financial violations was carried out, which proved the average annual changes in the volume of the number of accrued violations for the years 2019-2023 and allowed us to make a forecast for 2026. The results of the foresight analysis show that the volume of financial violations in 2026 may reach the level of UAH 68,956.5 thousand. Accounting criminal and administrative violations by types of corruption during 2019-2023 were studied. The structural analysis of violations for 2019-2022 shows that the top three corruption methods included: an offer, a promise or the granting of an undue advantage to an official (21,9%); failure to take appropriate measures to combat corruption crimes (15,7%); declaring false information (12,8%). The analysis confirmed the significance of anti-corruption audits of companies and the formation of an anti-corruption independent audit system.